(untitled) - Gitterman, Alex; Gitterman, Alex (New York, 2001)
Includes bibliographical references and indexes.; Neal A. Newfield, Ph.D., LICSW (Giver) ; Social work with vulnerable and resilient populations / Alex Gitterman -- Acquired immune deficiency syndrome (AIDS) / George S. Getzel and Stephen W. Willroth -- Alcoholism and other drug addictions / Meredith Hanson -- Borderline personality / Nina Rovinelli Heller and Harriette C. Johnson -- Chronic physical illness and disability / Grace H. Christ, Mary Sormanti, and Richard B. Francoeur -- Depression / Joy Callahan and Joanne E. Turnbull -- Developmental disabilities / Claudia L. Moreno -- Eating problems / Barbara van Bulow and Susan Braiman -- Learning disabilities / Naomi Pines Gitterman --Schizophrenia / Ellen Lukens -- Adolescent pregnancy / Bruce Armstrong -- Adult corrections / C. Aaron McNeece and Albert R. Roberts -- Child abuse and neglect / Lynn Videka-Sherman and Michael Mancini -- Children in foster care / Ernst O. VanBergeijk and Brenda G. McGowan -- Crime victims and victim services / Albert R. Roberts and Jacqueline Corcoran -- Death of a child / Barbara Oberhofer Dane -- Death of a parent / Nancy Boyd Webb -- Divorce / Ellen B. Bogolub -- Families in sparsely populated areas / Joanne Gumpert and Joan E. Saltman -- Family caregivers of the frail elderly / Ronald W. Toseland, Gregory C. Smith, and Philip McCallion -- Gay and lesbian persons / Carol T. Tully -- Homeless people / Marcia B. Cohen -- Immigrants and refugees / Diane Drachman and Angela Shen-Ryan -- Intimate partner abuse / Bonnie E. Carlson and Deborah Choi -- Older persons in need of long-term care / Toby Berman-Rossi -- Single parenthood / Aurora P. Jackson -- Suicide and suicidal behavior / Andre Ivanoff and Prudence Fisher -- Women of color / Edith Lewis, Lorraine Gutierrez and Izumi Sakamoto -- Work and job jeopardy / Sheila H. Akabas and Lori Bikson
Keywords: Social service -- United States; Social work with people with social disabilities -- United States; Social Work -- methods -- United States -- Case Report; Life Change Events -- United States -- Case Report; Mental Disorders -- psychology -- United States -- Case Report; Dịch vụ xã hội -- Mỹ (Hoa Kỳ); Công tác xã hội với người khuyết tật -- Mỹ (Hoa Kỳ)